The effects of the implementation order of implicit and explicit learning methods on learners' task enjoyment and motor skill acquisition - Matsuura, Yuki; Matsuoka, Hiroki; Isa, Yoshifumi; Sakairi, Yosuke (Frontiers in Sports and Active Living, 2025)
PurposeThis study aimed to explore the effect of the order of two learning methods (one based on implicit and another on explicit learning) on students' enjoyment and ability to acquire motor skills in gymnastics. Apparatus gymnastics courses for pre-service teachers were analyzed using information and communication technology.MethodsThe participants were 21 pre-service teachers in Japan. They were divided into two groups with equal skill levels, with the order of learning method alternating between the groups. Seven lessons were conducted in total. Changes in enjoyment of learning mat exercises, physical sensation during practice, and self-evaluation of skill progress were examined before and after class.ResultsIn implicit learning, the learners enjoyed activities without concern about the presence of others; however, their self-evaluation of skill progress was lower than that in explicit learning. In explicit learning, learners enjoyed activities less than in implicit learning; however, their self-evaluation of skill progress was higher than that in implicit learning, and they tried to perform tasks with higher-level skills. This was possibly because learners experienced enjoyment without concern about the presence of others implicit learning, followed by the opportunity to improve their self-evaluation and attempt higher-level tasks in explicit learning.ConclusionThe findings suggest optimal instructional strategies should implement implicit learning to foster enjoyment and sensory-motor exploration, followed by explicit learning to enhance progress self-evaluation and promote performance of advanced skill challenges.